ANALYSIS OF THE DIFFICULTIES OF PHONEME-GRAPHEME CORRESPONDENCE IN READING ENGLISH FOR GRADE VI STUDENTS AT ELEMENTARY SCHOOL 106166 MARINDAL 2 - Hutapea, Indah Jesica; Girsang, Asaria Semaya; Nainggolan, Fadhillah Azzahra; Rambe, Rizki Muda Ananda; Simanjuntak, Eva Betty; Nasution, Dea Yuanita (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2026)
Mastering reading skills is a crucial foundation in learning English as a Foreign Language (EFL), particularly at the elementary school level. At SDN 106166 Marindal 2, sixth-grade students are challenged to master vocabulary and pronunciation as a foundation. However, this learning process faces specific obstacles directly related to the linguistic systems of the two languages being studied. This research is urgently needed to comprehensively analyze the difficulties in phoneme-grapheme correspondence and formulate pedagogical recommendations that focus on the methodological transition (from repetition to phonics) and a student-centered approach, which has been proven effective in addressing reading and pronunciation difficulties in sixth-grade students at SDN 106166 Marindal 2.